EFEKTIVITAS SWEDISH MASSAGE DENGAN LAVENDER OIL TERHADAP KEKUATAN OTOT EKSTREMITAS PASIEN PASCA STROKE - Sari, Novianti '; Karim, Darwin '; Elita, Veny ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The aim of this research was to determine the effectiveness swedish massage with lavender oil to the limb muscle strength of post stroke patients. The design of this research was “Quasy experimental design” with “Pre test-post test with control group”. The research was conducted in the working area of Harapan Raya community health center. The total sample were 30 respondents who fit the inclusion criteria and chosen by purposive sampling. Measuring instrument that used in both groups was muscle strength scale of Medical Research Council Scale. The analysis was used univariate and bivariate analyzes by using Wilcoxon and Mann Whitney test. The result showed that there was a significant increased of limb muscle strength in experimental group which has given swedish massage with p value (0,000) < α (0,05). It can be concluded that the swedish massage with lavender oil was effective to improve limb muscle strength for post stroke patients. Based on this research the therapy swedish massage with lavender oil can be used as a non pharmacological therapy to increase limb muscle strength in patients with post stroke. Keywords: Muscle strength, post stroke, swedish massage